Development and Storage Studies of Aonla (Emblica officinalis Gaertn.) based Ready to Serve (RTS) Using Different Sweeteners - Meena, V. S.; Sharma, P. C.; Yadav, V. S.; Meena, R. S.; Mahawar, Manoj; Bhushan, Bharat; Jalgaonkar, Kirti; Kannaujia, Pankaj; Meena, K. K. (International Journal of Bio-resource and Stress Management, 2017)
The investigation on preparation of ready-to-serve beverage from Aonla using sugar substitutes was conducted at ICAR-CIPHET, Abohar (Punjab) during 2014–15. The experiment was laid out in completely randomised design with three replications and four treatments viz., sucrose, aspartame, sucralose and stevia with 50% juice made by blending of 60% of aonla, 20% pomegranate and 20% aloe vera. The RTS beverage with no sugar was the control. Sugar substitutes were used in place of sugar based on sugar equivalents. The required quantities of juice, sugar substitutes, water and citric acid were calculated. Strained fruit juice and freshly prepared sugar syrup were mixed together in the proportion as per the recipes on weight basis. The prepared RTS beverages were stored up to six months and analysed for chemical composition and sensory quality attributes sensory quality attributes at 0, 30, 60, 90, 120, 150 and 180 days intervals at ambient conditions. At the end of storage, RTS with stevia 4% was found best among all in term biochemical and sensory quality. During storage period, the TSS, acidity and total sugars increased, while pH, and ascorbic acid decreased. The RTS beverage had storage stability up to six months. The developed RTS could be recommended for the large scale production at industrial level.